X‐linked sideroblastic anemia due to ALAS2 intron 1 enhancer element GATA‐binding site mutations. Issue 3 (20th November 2013) - Campagna, Dean R.; de, Charlotte I.; Schmitz‐Abe, Klaus; Sweeney, Marion; Sendamarai, Anoop K.; Schmidt, Paul J.; Heeney, Matthew M.; Yntema, Helger G.; Kannengiesser, Caroline; Grandchamp, Bernard; Niemeyer, Charlotte M.; Knoers, Nine V.A.M.; et al.
<x xml:space="preserve">Abstract</x> X‐linked sideroblastic anemia (XLSA) is the most common form of congenital sideroblastic anemia. In affected males, it is uniformly associated with partial loss‐of‐function missense mutations in the erythroid‐specific heme biosynthesis protein 5‐aminolevulinate synthase 2 (ALAS2). Here, we report five families with XLSA owing to mutations in a GATA transcription factor binding site located in a transcriptional enhancer element in intron 1 of the ALAS2 gene. As such, this study defines a new class of mutations that should be evaluated in patients undergoing genetic testing for a suspected diagnosis of XLSA. Am. J. Hematol. 89:315–319, 2014. © 2013 Wiley Periodicals, Inc.